2003
DOI: 10.1074/jbc.m303772200
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Amino-terminal Region of the PDE4D5 cAMP Phosphodiesterase Isoform Confers Preferential Interaction with β-Arrestins

Abstract: Isoproterenol challenge of Hek-B2 cells causes a transient recruitment of the endogenous PDE4D isoforms found in these cells, namely PDE4D3 and PDE4D5, to the membrane fraction. PDE4D5 provides around 80% of the total PDE4D protein so recruited, although it only comprises about 40% of the total PDE4D protein in Hek-B2 cells. PDE4D5 provides about 80% of the total PDE4D protein found associated with ␤-arrestins immunopurified from Hek-B2, COS1, and A549 cells as well as cardiac myocytes, whereas its overall lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
140
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 52 publications
6
140
0
Order By: Relevance
“…ENGELS et al [266] have also reported induction of PDE4 isogenes in U937 and Jurkat T-cells in response to prolonged exposure to dibutyryl cAMP, and, more recently, the same phenomenon was documented in guinea pig macrophages [266], human T-lymphocytes [156], human neutrophils [256] and human ASM cells [157]. In the latter study, upregulation of the PDE4D5 splice variant was described, and this may be of particular significance given that this isoform interacts preferentially with b-arrestins and may play a role in b 2 -adrenoceptor desensitisation (see above) [237,238].…”
Section: Upregulation Of Phosphodiesterasementioning
confidence: 84%
See 2 more Smart Citations
“…ENGELS et al [266] have also reported induction of PDE4 isogenes in U937 and Jurkat T-cells in response to prolonged exposure to dibutyryl cAMP, and, more recently, the same phenomenon was documented in guinea pig macrophages [266], human T-lymphocytes [156], human neutrophils [256] and human ASM cells [157]. In the latter study, upregulation of the PDE4D5 splice variant was described, and this may be of particular significance given that this isoform interacts preferentially with b-arrestins and may play a role in b 2 -adrenoceptor desensitisation (see above) [237,238].…”
Section: Upregulation Of Phosphodiesterasementioning
confidence: 84%
“…Thus, following agonism of b 2 -adrenoceptors expressed in HEK 293 cells, a b-arrestin/PDE4D complex forms and is recruited to the receptor, where it limits activation of the cAMP/PKA cascade by simultaneously suppressing AC activity, through receptor desensitisation, and accelerating the removal of cAMP, through enhanced degradation [236]. It appears that the unique amino-terminal region of PDE4D5 confers preferential interaction with barrestins and may represent the normal binding partner of this scaffold in intact cells [237]. This targeting of PDE4D to the b 2 -adrenoceptor complex may have highly discrete functional implications for the cell as it will selectively regulate the activity of a pool of PKA that is co-localised to the same subcellular microdomain via an interaction with an AKAP [238].…”
Section: Activation Of Pkgmentioning
confidence: 99%
See 1 more Smart Citation
“…Houslay and colleges demonstrated that inhibition of PDE-4 affects CNS responses including depression, schizophrenia and memory (22)(23)(24)(25)(26). ␤-arrestin-2 can form stable complex with PDE-4s (27,28), and PDE-4D5 is the preferred binding partner of ␤-arrestin-2 (29). In this study, we reveal a role of ␤-arrestin-2/PDE-4D complex in feedback regulation of amygdalar PKA activity in response to fear conditioning and demonstrate ␤-arrestin-2 is critical for the formation of associative fear memory.…”
mentioning
confidence: 99%
“…For example, the NTR of PDE4A4/5 and PDE4D4 interacts with the SH3 domain of the Src family of tyrosine kinases such as Lyn, Fyn, and Src (16,17). The NTR of PDE4D5 interacts with ␤-arrestin (18) or with the receptor for activated protein kinase C (RACK1) (19), and the NTR of PDE4D4/5 interacts with Aryl hydrocarbon receptorinteracting protein (AIP) (20). The NTR of PDE4A1, a brainspecific isoform, is known to be the only PDE4 isoform that interacts with the membrane directly and is targeted to the Golgi complex and its associated vesicles through the two helices (helices 1 and 2) within the NTR (21,22).…”
mentioning
confidence: 99%